Development of literacy culture in multi-cultural country - Ragil Tri Atmi, Meinia Prayesti Kurniasari, Koko Srimulyo, Dessy Harisanty, (Opción, 2020)
Illiteracy still becomes a problem in various developing countries. Indonesia as a multi-cultural country needs to make efforts to eradicate illiteracy, one of which is through the development of a literacy culture. The purpose of this research is to know the condition and role of government, public and community groups in the development of literacy culture. The government, public and community groups have made efforts in the development of literacy culture, one of which is the creation of TBM. However, the role and performance have not been optimal due to the development gap, budget constraints, and lack of information and public awareness about the importance of literacy culture.